Level of Emotional Intelligence among a Sample of Secondary School Teachers at Al Koura District- Jordan (Global Journal of Human-Social Science, 2018)
The main objective of the current study was to investigate the levels of emotional intelligence among a sample of secondary school teachers at Al Koura Educational district in light of their gender qualification and teaching experience Sample of the study consisted of 283 male and female teachers selected suing random sampling in the academic year 2017 2018 The results of the study indicated that teachers reported moderate levels of emotional intelligence It is also indicated that there is no significant differences in emotional intelligence levels due to gender and qualification while significant differences were found in emotional intelligence levels due to teaching experience in favor of more teacher s experiences
Keywords: emotional intelligence; secondary school teachers